2022
DOI: 10.1111/pace.14498
|View full text |Cite
|
Sign up to set email alerts
|

Selvester QRS score predicts improvement of LVEF in atrial fibrillation patients with systolic heart failure

Abstract: Background Left‐ventricular systolic dysfunction (LVSD) comorbid with atrial fibrillation is reversible, but recovery is limited in a subset of patients. The Selvester QRS (S‐QRS) score is an electrocardiogram‐based assessment that reportedly reflects myocardial scar/damage. We evaluated the predictability of S‐QRS score for the recovery of left‐ventricular ejection fraction (LVEF) in persistent AF (PeAF) patients with LVSD undergoing catheter ablation (CA). Method CA was performed in 51 PeAF patients with red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In the present study, the QRS score ≥3 group showed significantly higher IMR in comparison to the QRS 0-2 group. Selvester's QRS score reflects myocardial damage influenced by diverse factors, including previous MI, chronic atrial fibrillation, and heart failure ( 6 , 14 ). In this study, patients in the QRS score ≥3 group exhibited higher rates of previous MI, chronic atrial fibrillation, and higher NT-pro BNP in comparison to the QRS score 0-2 group.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the present study, the QRS score ≥3 group showed significantly higher IMR in comparison to the QRS 0-2 group. Selvester's QRS score reflects myocardial damage influenced by diverse factors, including previous MI, chronic atrial fibrillation, and heart failure ( 6 , 14 ). In this study, patients in the QRS score ≥3 group exhibited higher rates of previous MI, chronic atrial fibrillation, and higher NT-pro BNP in comparison to the QRS score 0-2 group.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded patients with left or right bundle branch block, in line with other studies that excluded them due as the ECGs of these patients were not suitable for the analyses. Conversely, some investigations included them using their specific scoring criterion if the ECG was LBBB or RBBB type ( 13 , 14 ). We conducted a further analysis including patients with left or right bundle branch block employing each Selvester QRS score criterion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations